Phytochemical Analysis and Antioxidant Potential of Ethylacetate Extract of Tamarindus Indica (Tamarind) Leaves by Frap Assay - Mubarak Muhammad Dahiru; Hadiza Ahmadi; Maimuna Umar Faruk; Huzaifa Huzaifa Aminu Hamman; Abreme Gahana Charles (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
Oxidative stress is characterized by an imbalance in the generation of free radicals and their subsequent elimination by endogenous antioxidants. It is a characteristic of several diseases, especially during the progression stage, which can lead to fatal effects. This study aims to investigate the phytochemical components and antioxidant capability of Tamarindus indica and assess its capability as a candidate for managing diseases associated with oxidative stress. The gravimetric method detected and quantified phytochemicals, while the reducing power assay determined the antioxidant potential. Saponins, steroids, and flavonoids were detected in 6.83 ±0.44, 4.30 ±0.60, and 10.17% ±0.60, respectively, without alkaloids, glycosides, and terpenoids. The antioxidant test showed a concentration-dependent increase in absorbance of both the extract and standard (Ascorbic acid). However, Ascorbic acid had higher absorbance. At 100% concentration, the sample had an absorbance of 0.388 ±0.022, which was lower than the absorbance of Ascorbic acid (0.411 ±0.009) at 40% concentration. It can be concluded that Tamarind leaves could be utilized to manage diseases associated with oxidative stress, evidenced by their antioxidant potential credited to the phytochemical content of the leaves. However, there is a need for further studies to ascertain the exact compounds and their modes of action.